ASSESSMENT OF TRAINING COMPETENCE, MENTAL TOUGHNESS, AND EMOTIONAL STABILITY OF IRAQI PREMIER LEAGUE HANDBALL COACHES - Kadhim Abdulkareem, Dr. Ahmed; Hani Abed Al Gburi, Dr. Ayman (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The significance of this study lies in assessing the levels of training competence, mental toughness, and emotional stability among coaches in the Iraqi Premier League for handball. The objectives of the study were To develop scales for training competence and mental toughness among Iraqi Premier League handball coaches, To assess the training competence, mental toughness, and emotional stability of Iraqi Premier League handball coaches, To determine the levels of training competence, mental toughness, and emotional stability among Iraqi Premier League handball coaches.Based on the results and interpretations of the current research, several conclusions were drawn, including:- The scales for training competence and mental toughness, consisting of (20) items each, demonstrated sufficient reliability and validity in measuring the training competence and mental toughness of Iraqi Premier League handball coaches.- Iraqi Premier League handball coaches exhibit adequate training competence, mental toughness, and emotional stability.